Impact of endometriosis on quality of life and work productivity: a multicenter study across ten countries. - Nnoaham, K; Hummelshoj, L; Webster, P; d'Hooghe, T; de Cicco Nardone, F; de Cicco Nardone, C; Jenkinson, C; Kennedy, S; Zondervan, K (2011)
OBJECTIVE: To assess the impact of endometriosis on health-related quality of life (HRQoL) and work productivity. DESIGN: Multicenter cross-sectional study with prospective recruitment. SETTING: Sixteen clinical centers in ten countries. PATIENT(S): A total of 1,418 premenopausal women, aged 18-45 years, without a previous surgical diagnosis of endometriosis, having laparoscopy to investigate symptoms or to be sterilized. INTERVENTION(S): None. MAIN OUTCOME MEASURE(S): Diagnostic delay, HRQoL, and work productivity. RESULT(S): There was a delay of 6.7 years, principally in primary care, between onset of symptoms and a surgical diagnosis of endometriosis, which was longer in centers where women received predominantly state-funded health care (8.3 vs. 5.5 years). Delay was positively associated with the number of pelvic symptoms (chronic pelvic pain, dysmenorrhoea, dyspareunia, and heavy periods) and a higher body mass index. Physical HRQoL was significantly reduced in affected women compared with those with similar symptoms and no endometriosis. Each affected woman lost on average 10.8 hours (SD 12.2) of work weekly, mainly owing to reduced effectiveness while working. Loss of work productivity translated into significant costs per woman/week, from US$4 in Nigeria to US$456 in Italy. CONCLUSION(S): Endometriosis impairs HRQoL and work productivity across countries and ethnicities, yet women continue to experience diagnostic delays in primary care. A higher index of suspicion is needed to expedite specialist assessment of symptomatic women. Future research should seek to clarify pain mechanisms in relation to endometriosis severity.